Extended high resolution study of 28SiH4 in the region of the octad stretching–bending bands; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 338 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Nikolaeva N. I. Natalya Ivanovna; Sydow С. Christian; Bauerecker S. (2025, 2025)
The infrared spectra of 28SiH4 were measured at varied experimental conditions with a Bruker Fourier transform infrared spectrometer IFS125HR and analyzed in the 2800–3400 cm−1 region where eight sub-bands of the four stretching–bending bands of the octad are located. The 5670 transitions (Jmax=27) belonging to these sub-bands were assigned (which is 5.5 times higher in comparison with the amount of corresponding data known from the literature) in the recorded experimental spectra and theoretically reproduced by a set of 130 parameters (band centers, rotational, centrifugal distortion, tetrahedral splitting and resonance interaction parameters) obtained from the weighted fit with the drms deviation of 4.7×10−4 cm−1. A list of assigned experimental transitions is presented as the Supplementary data to this paper